Meta-Revision: The New Paradigm of Faustian Stories - Getlík, Peter; Andričíková, Markéta (Communication Today, 2021)
The aim of the study is to introduce and verify the perspective of the “meta-revision” concept for an analysis of adaptations (revisions) in the intermediality discourse. The issue of meta-revisions is presented through evident moral dichotomy in Faustian stories which are frequently adapted in Western culture. Besides many Faustian adaptations that are variable in plot yet traditional in the moral manifestations, we recognise only a few cases that question the exclusivity of conventional Christian ethics. Verification of the concept of “meta-revision” is done especially through the analysis of several film structures, whereas two of them bear significant meta-revisionist features: we identify the meta-revision of cultural self-identification with the hero (The Imaginarium of Doctor Parnassus by Terry Gilliam) and meta-revision of cultural self-identification with the villain (Mephisto by István Szabó; based on the novel by Klaus Mann). As a conclusion of the study the three distinctive aspects of meta-revision applicable in further research on adaptations are defined.